2023
DOI: 10.1155/2023/9956847
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Household Daily Water Consumption Dynamics in the Tropical Environment

Abstract: Understanding daily water use determinants is critical to sustainable water access and its efficient use at household level. To pursue this objective, primary data were generated through a survey of 276 respondents across the 5 quarters into which the city of Iwo is divided. 67.5% of the respondents were between 19 and 45 years old while 35.5% were between 46 and 65 years old and the remaining 3.9% comprised of those above 65 years. The results of factor analysis (FA) showed that 12 of the 40 factors analyzed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Factor Analysis (FA) was chosen for this analysis due to its ability to identify underlying factors or dimensions within a dataset and to determine the variables that contribute most significantly to residents’ perceptions of the environmental consequences of quarry activities. The statistic has been successfully used to achieve this same purpose by Ogunbode et al, 23 Ogunbode et al 24 and Sigudla and Maritz. 25 A dataset is ‘factorable’ indicated that it can be decomposed or factorised to reveal underlying structures or latent variables that explain patterns within the data.…”
Section: Discussionmentioning
confidence: 99%
“…Factor Analysis (FA) was chosen for this analysis due to its ability to identify underlying factors or dimensions within a dataset and to determine the variables that contribute most significantly to residents’ perceptions of the environmental consequences of quarry activities. The statistic has been successfully used to achieve this same purpose by Ogunbode et al, 23 Ogunbode et al 24 and Sigudla and Maritz. 25 A dataset is ‘factorable’ indicated that it can be decomposed or factorised to reveal underlying structures or latent variables that explain patterns within the data.…”
Section: Discussionmentioning
confidence: 99%
“…An all-encompassing understanding of the diverse factors influencing water resource management at various spatial and temporal levels is a prerequisite for achieving SDG Target 6 (Akuoko-Asibey et al 1993, United Nations Development Programme (UNDP) 2016, Gumez et al 2019, Ogunbode et al 2023). According to the UNDP (2016), SDG 6 emphasizes the importance of water-related ecosystems, stressing the need to protect and restore rivers, lakes, and wetlands.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Martinez-Santos (2017) submitted from his investigation in southern Mali that water demand on a daily basis is greatly influenced by diverse variables such as household size, status of water accessibility, seasonal variation, and the economic power of the household head, among others. According to Ifabiyi (2014, 2017) and Ogunbode et al (2023), household characteristics offered significant explanations for household daily water use in Iwo, Nigeria.…”
Section: Introductionmentioning
confidence: 99%
“…Existing empirical evidence (Bayu et al, 2020;Puskás et al, 2021;Widyarani et al, 2022& Ogunbode et al, 2023 indicated that the majority of water supply projects fail in rural communities within three years after development. These water supply projects fail due to the least interest of community members regarding decision-making, site identification, planning, execution, monitoring, evaluation and management process and, above all, unawareness and lack of basic technical and management skills (Iduseri et al, 2021).…”
Section: Introductionmentioning
confidence: 99%